Pregled fizikalne terapije s poudarkom na indiciranosti in kontraindiciranosti pri bolnikih z rakom - Moharić, Metka (Rehabilitacija (Ljubljana), 2008)
Physical therapy is an integral part of rehabilitation of patients with neurologic and musculoskeletal injuries and disabilities, whatever their reason is. Cancer rehabilitation addresses physical impairments related to tumor effects or to cancer treatment. The fact that impairments are due to cancer might alter their management very little. Warnings against treating cancer patients with many physical modalities are ubiquitous in the rehabilitation literature. Most precautions are not supported by empiric data. A climate of exaggerated caution too often limits cancer rehabilitation. Specific therapeutic precautions reflect a fear of injuring patients, or worse, spreading their cancer. If the clinical context warrants a trial of physical modalities, the option should not be reflexively abandoned because of unsubstantiated warnings.
Keywords: fizikalna terapija; indikacije; kontraindikacije; rak (medicina)